2013
DOI: 10.1007/s00253-013-4878-x
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological production of sphingoid bases and their applications

Abstract: Sphingolipids are not only essential components of biological membranes but also play numerous other vital functions in living cells. Moreover, they are major constituents of the outermost layer of human epidermis which acts as permeability barrier of the skin. Therefore, they have a high potential to be used in a wide variety of application fields such as antibacterial and antifungal agents, active pharmaceutical ingredients of therapeutics as well as active ingredients in cosmeceutical or nutraceutical formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Previous studies have also demonstrated that changes in bile acids, phosphatidylcholine, and amino acids occur in acute pancreatitis [ 27 , 31 , 32 ], thus confirming our present findings. However, few researchers have investigated differences in metabolites between severe and mild cases.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have also demonstrated that changes in bile acids, phosphatidylcholine, and amino acids occur in acute pancreatitis [ 27 , 31 , 32 ], thus confirming our present findings. However, few researchers have investigated differences in metabolites between severe and mild cases.…”
Section: Resultssupporting
confidence: 93%
“…The increased serum level of sphingasine may be caused by the tryptic hydrolysis‐induced rupture of lots of cells. Capryloyl choline and decanoyl choline belong to cholines, which are both the esterification products of choline and fatty acid under the roles of choline acetyltransferase . The choline metabolism pathway is an important pathway of inflammation responses.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingoid bases can be synthesized chemically in a complex and cost-intensive way. An alternative process is based on the fermentation of yeast 1 and ensures the distinct stereochemical configuration of the two asymmetrical carbon atoms of the molecule, which is also found in nature and in human skin.…”
Section: Introductionmentioning
confidence: 99%